Hubungan lamanya hemodialisis dengan tingkat depresi pada pasangan hidup pasien gagal ginjal kronik di RSUP Prof. Dr. R. D. Kandou Manado - Tartum, Vicka V. A.; Kaunang, Theresia M. D.; Elim, Christofel; Ekawardani, Neni (e-CliniC, 2016)
Abstract: Depression is a disturbance in the function of human nature associated with feelings of sadness and accompanying symptoms, including changes in sleep patterns and appetite, anhedonia, concentration, psychomotor, fatigue, despair and helplessness. Depression can be obtained by any person, including a person suffering from chronic diseases such as chronic renal disease requiring hemodialysis therapy for life. However, the impact of depression was not only felt by the patient, but also the patient's family, especially spouses of patients would be very easy to get depressed as a result of seeing a loved one suffer, so will affect the support and motivation given to patients, especially in patients undergoing hemodialysis should undergo dialysis for life, so a lot of depression in patients and their families, especially spouses of patients. This study aimed to determine the relationship of the length of hemodialysis with the level of depression in spouses of hemodialysis patients in Prof. Dr. R. D. Kandou Hospital Manado. This was an observational analystical study with a cross sectional design. This study used Hamilton Depression Rating Scale questionaire (HDRS). Data were processed by using SPSS 20.0. The chi-square analysis test showed a p value of 0.105 (p > 0.05). Conclusion: There was no correlation between the duration of hemodialysis with the degree of depression of chronic kidney failure patient’s live spouses. Keywords: depression, chronic kidney disease, hemodialysis, spouse. Abstrak: Depresi adalah terganggunya fungsi manusia yang berkaitan dengan alam perasaan yang sedih dan gejala penyertanya, termasuk perubahan pada pola tidur dan nafsu makan, anhedonia, konsentrasi, psikomotor, kelelahan rasa putus asa dan tidak berdaya. Depresi bisa didapatkan oleh setiap orang termasuk seseorang yang menderita penyakit kronik seperti penyakit ginjal kronik yang membutuhkan terapi hemodialisis seumur hidup. Dampak depresi pun tidak hanya dirasakan oleh pasien, keluarga pasien terutama pasangan hidup pasien akan sangat mudah mendapatkan depresi akibat melihat orang yang dicintai menderita, sehingga akan memengaruhi dukungan dan motivasi yang akan diberikan kepada pasien, terutama pada pasien yang menjalani hemodialisis yang harus menjalani proses cuci darah seumur hidup, sehingga banyak terjadi depresi pada pasien dan keluarganya terutama pasangan hidup pasien. Penelitian ini bertujuan untuk mengetahui hubungan lamanya hemodialisis dengan tingkat depresi pada pasangan hidup pasien hemodialisis di RSUP Prof. Dr. R. D. Kandou Manado. Metode penelitian yang digunakan ialah analitik observasional dengan pendekatan potong lintang. Penelitian ini menggunakan kuesioner Hamilton Depression Rating Scale (HDRS) dan data diolah menggunakan SPSS 20.0. Uji analisis chi-square mendapatkan nilai p sebesar 0,105 (p >0,05). Simpulan: Tidak terdapat hubungan antara lama hemodialisis dengan tingkat depresi pasangan hidup pasien penyakit ginjal kronik. Kata kunci: depresi, penyakit ginjal kronik, hemodialisis, pasangan hidup